Cooperative Learning and Attitude towards Research in University Students of Business Sciences - Loza Ticona, Renzi Marilu (2024)
The purpose of this study was to examine the relationship between cooperative learning and attitude towards research in university business students in Tacna, Peru. Based on the existing literature, the dimensions of these variables were identified, using the Constructivist Theory of Learning and the Attitude Reinforcement Theory as a conceptual framework, in order to propose a model of hypothesized relationships between them. To validate this model, a structural equation approach was employed, using a probability sample of 614 university students. The findings revealed a significant positive correlation between cooperative learning and attitude toward research (rs=.663), indicating a high level of fit between the empirical data and the proposed theoretical model, based on structural equations, to explain the relationship between cooperative learning and attitude toward research. These results have practical implications relevant for both university students and educators in higher education institutions in Tacna.